Polymorphic variants of SCN1A and EPHX1 influence plasma carbamazepine concentration, metabolism and pharmacoresistance in a population of kosovar albanian epileptic patients - Daci, A.; Beretta, G.; Vllasaliu, D.; Shala, A.; Govori, V.; Norata, Giuseppe; Krasniqi, S. (Public Library of Science, 2015)
Aim: The present study aimed to evaluate the effects of gene variants in key genes influencing pharmacokinetic and pharmacodynamic of carbamazepine (CBZ) on the response in patients with epilepsy. Materials & Methods: Five SNPs in two candidate genes influencing CBZ transport and metabolism, namely ABCB1 or EPHX1, and CBZ response SCN1A (sodium channel) were genotyped in 145 epileptic patients treated with CBZ as monotherapy and 100 age and sex matched healthy controls. Plasma concentrations of CBZ, carbamazepine-10,11-epoxide (CBZE) and carbamazepine-10,11-trans dihydrodiol (CBZD) were determined by HPLC-UV-DAD and adjusted for CBZ dosage/kg of body weight. Results: The presence of the SCN1A IVS5-91G>A variant allele is associated with increased epilepsy susceptibility. Furthermore, carriers of the SCN1A IVS5-91G>A variant or of EPHX1 c.337T>C variant presented significantly lower levels of plasma CBZ compared to carriers of the common alleles (0.71±0.28 vs 1.11±0.69 μg/mL per mg/Kg for SCN1A IVS5-91 AA vs GG and 0.76±0.16 vs 0.94±0.49 μg/mL per mg/Kg for EPHX1 c.337 CC vs TT; P<0.05 for both). Carriers of the EPHX1 c.416A>G showed a reduced microsomal epoxide hydrolase activity as reflected by a significantly decreased ratio of CBZD to CBZ (0.13±0.08 to 0.26±0.17, p<0.05) also of CBZD to CBZE (1.74±1.06 to 3.08±2.90; P<0.05) and CDRCBZD (0.13±0.08 vs 0.24±0.19 μg/mL per mg/Kg; P<0.05). ABCB1 3455C>T SNP and SCN1A 3148A>G variants were not associated with significant changes in CBZ pharmacokinetic. Patients resistant to CBZ treatment showed increased dosage of CBZ (657±285 vs 489±231 mg/day; P<0.001) but also increased plasma levels of CBZ (9.84±4.37 vs 7.41±3.43 μg/mL; P<0.001) compared to patients responsive to CBZ treatment. CBZ resistance was not related to any of the SNPs investigated. Conclusions: The SCN1A IVS5-91G>A SNP is associated with susceptibility to epilepsy. SNPs in EPHX1 gene are influencing CBZ metabolism and disposition. CBZ plasma levels are not an indicator of resistance to the therapy.